Faunistic analysis of Carabidae and Staphylinidae (Coleoptera) in five agroecosystems in northeastern São Paulo state, Brazil - Cividanes, Francisco Jorge; Barbosa, José Carlos; Ide, Sérgio; Perioto, Nelson Wanderlei; Lara, Rogéria Inês Rosa (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this study was to determined species composition and community structure of Carabidae and Staphylinidae in five areas of forest fragment and soybean/corn crops or orange orchard, from December 2004 to May 2007. Beetles were captured in pitfall traps distributed along two parallel transects of 200 m in length, placed across crop land/forest boundary fragment, with 100 m each. The Shannon-Wiener diversity and evenness indexes and Morisita similarity index were calculated. The carabids Abaris basistriatus Chaudoir, Calosoma granulatum Perty, Megacephala brasiliensis Kirby, Odontochila nodicornis (Dejean) and Selenophorus seriatoporus Putzeys. are dominant and are widely distributed in northeastern São Paulo state, Brazil. Point-scale species diversity was greatest at the transition between forest fragment and cultivated area. The carabid and staphylinid communities of the forest fragment were more similar to the community of orange orchard than that of soybean/corn crops.
Keywords: Citrus sinensis; Glycine max; Zea mays; diversity; no-tillage; similarity